(untitled) (International Congress on Economics, Management and Business Studies, 2026)
The stability and sustainable development of the banking sector largely depend on the quality of credit portfolios and the effectiveness of credit risk management mechanisms. Since lending activities constitute the primary source of income for commercial banks, the deterioration of credit portfolio quality may lead to an increase in non-performing loans, reduced profitability, and weakened financial stability. In recent years, the banking sector of Uzbekistan has experienced rapid growth in lending volumes, which has simultaneously increased the importance of maintaining high-quality credit portfolios and strengthening risk management practices. Consequently, improving the quality of credit portfolios has become one of the key priorities for ensuring the resilience and competitiveness of commercial banks [1].